2008
DOI: 10.1021/jm701575k
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Potent, Selective, and Orally Active Leukotriene A4 Hydrolase Inhibitor with Anti-Inflammatory Activity

Abstract: LTA 4H is a ubiquitously distributed 69 kDa zinc-containing cytosolic enzyme with both hydrolase and aminopeptidase activity. As a hydrolase, LTA 4H stereospecifically catalyzes the transformation of the unstable epoxide LTA 4 to the diol LTB 4, a potent chemoattractant and activator of neutrophils and a chemoattractant of eosinophils, macrophages, mast cells, and T cells. Inhibiting the formation of LTB 4 is expected to be beneficial in the treatment of inflammatory diseases such as inflammatory bowel disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 54 publications
1
29
0
8
Order By: Relevance
“…In order to synthesize the compound 2, we commenced our investigation by employing a Wittig reaction between aldehydes 3 and the corresponding phosphonium salt 5, derived from the commercially available 2-(4-hydroxyphenyl) ethanol [6,7]. However, the Wittig reaction failed to afford our desired product 2 presumably due to low reactivity of the electron-rich benzaldehydes 3 (Scheme 2) [8].…”
Section: Scheme 1 Retrosynthetic Approach Of Broussonone a (1)mentioning
confidence: 99%
“…In order to synthesize the compound 2, we commenced our investigation by employing a Wittig reaction between aldehydes 3 and the corresponding phosphonium salt 5, derived from the commercially available 2-(4-hydroxyphenyl) ethanol [6,7]. However, the Wittig reaction failed to afford our desired product 2 presumably due to low reactivity of the electron-rich benzaldehydes 3 (Scheme 2) [8].…”
Section: Scheme 1 Retrosynthetic Approach Of Broussonone a (1)mentioning
confidence: 99%
“…These types of heterocyclic compounds exhibit antitumor (8,9) anti-inflammatory (10,11), antibacterial (12), antiviral (13), and antimicrobial (14) activities. Since this investigation deals with a new approach to synthesize these medicinally important heterocyclic compounds, it is essential to review the procedures reported in literature.…”
Section: Introductionmentioning
confidence: 99%
“…For the pharmacophore modeling studies, a set of LTA4H inhibitory activity data (IC50) spanning over 4 orders of magnitude (from 1 to 630,000 nM) were selected [8][9][10][11][12][13]. The dataset was divided into training set (Insert Fig 1) and test set (supplementary information Table1).…”
Section: Pharmacophore Generationmentioning
confidence: 99%